2013
DOI: 10.1016/j.vhri.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Pharmaceutical Care Intervention Versus Usual Care in Management of Nigerian Patients with Type 2 Diabetes

Abstract: The PC intervention was very cost-effective among patients with type 2 diabetes at the NGN 88,525 ($571.13) per QALY gained threshold, although considerable uncertainty surrounds these estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(90 citation statements)
references
References 18 publications
0
89
0
1
Order By: Relevance
“…Of the 30 articles included in the review , 21 were CEAs [16,[18][19][20][21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37]39], 4 were CUAs [17,26,38,40], 4 were CBAs [42][43][44][45], and 1 consisted of both CEA and CBA [41]. Among those studies, 7 were conducted in the United States [17,20,23,24,28,44,45], 9 in Europe [16,26,[31][32][33][34]37,41,43], 7 in Asia [25,27,29,30,35,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 30 articles included in the review , 21 were CEAs [16,[18][19][20][21][22][23][24][25][27][28][29][30][31][32][33][34][35][36][37]39], 4 were CUAs [17,26,38,40], 4 were CBAs [42][43][44][45], and 1 consisted of both CEA and CBA [41]. Among those studies, 7 were conducted in the United States [17,20,23,24,28,44,45], 9 in Europe [16,26,[31][32][33][34]37,41,43], 7 in Asia [25,27,29,30,35,…”
Section: Resultsmentioning
confidence: 99%
“…More than a half of the studies (n ¼ 17) conducted their economic analyses using the patient's perspective and at least one more perspectives such as societal (n ¼ 5) [21,25,31,40,41], government or payer (n ¼ 5) [28,30,31,34,40], and health care provider, for example, health system, hospital, or clinic (n ¼ 11) [16][17][18][19][21][22][23][24]27,29,41]. Trial analysis was the most frequently used methodology (n ¼ 16) [20,23,26,27,[29][30][31][32][33][36][37][38][39][40]42,44], followed by decision-tree model (n ¼ 5) [16,17,25,28,34] and observational analysis (n ¼ 5) [19,[21][22][23]35,41,…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of health economics, health-related QoL (HRQoL) is an important patient-reported outcome useful for the purpose of understanding the burden of chronic diseases such as diabetes [ 15 ]. HRQoL measures are useful in evaluating the efficacy, cost effectiveness, and net benefits of current healthcare programs and interventions [ 16 ], and have been found to be relevant in the economic evaluation of the cost effectiveness of buprenorphine patch in the management of moderate pain [ 17 ], early versus late total hip replacement [ 18 ], and in the comparison of intensive against conventional education and supervision for the self-management of asthmatic [ 19 ] and diabetic patients [ 20 ]. At present, several multi-attribute utility instruments (MAUIs) have been developed and used for the purpose of determining HRQoL in principle.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries with poorer health care systems, the cost of managing DM is considerable. In a recent randomized, controlled trial (RCT) in Nigeria, Adibe et al showed that pharmaceutical intervention with a multidisciplinary approach cost 8 8,525 Nigerian naira (571 US dollars) per quality-adjusted life years gained 4. Although this was 95% more cost effective compared with usual care (incremental cost of 10,623 Nigerian naira or 69 US dollars), it still represents a significant financial burden in a country where 68% of the population live below the international poverty line of 1.25 US dollars per day 5…”
Section: Introductionmentioning
confidence: 99%